2021
DOI: 10.3389/fenrg.2021.634321
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sensing Properties of Thermal Conductivity-Type CO2 Gas Sensors by Loading Multi-Walled Carbon Nanotubes Into Nano-Al2O3 Powders

Abstract: Response time is the key index of on-line monitoring system. To improve the response speed of traditional bead thermal conductivity CO2 sensor, this paper proposes to use multi-walled carbon nanotubes (MWCNTs) to improve the performance of gas sensor carrier. Nano-sized γ-Al2O3/CeO2 powder was synthesized by chemical precipitation method under the action of ultrasonic wave. SEM morphology reveals a particle size of 20–50 nm. MWCNTs were hydroxylated and the solution was then prepared by adding a certain amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The nanostructure of Al2O3/CeO2/MWCNTs was successfully prepared by the conventional chemical precipitation process under the impact of the ultrasonic wave for CO2 gas. The obtained results demonstrated that the thermal conductivity sensor has 9 and 13 s as a response and recovery durations subsequently which outcomes most of the commercially available CO2 sensors [65].The as prepared MWCNTs/ZnO by reflux method at 197 ºC in ethylene glycol is employed for methanol gas detection. A wide span of temperatures within 100-300 ºC was investigated for the sensing behavior where the best performance was gained at the latter CARBON NANO BASED MATERIALS AND THEIR COMPOSITES FOR GAS SENSING.. __________________________________________________________________________________________________________________ ________________________________________________ Egypt.…”
Section: Carbon Nanotubes/metal Oxides For Gas Sensingmentioning
confidence: 74%
See 1 more Smart Citation
“…The nanostructure of Al2O3/CeO2/MWCNTs was successfully prepared by the conventional chemical precipitation process under the impact of the ultrasonic wave for CO2 gas. The obtained results demonstrated that the thermal conductivity sensor has 9 and 13 s as a response and recovery durations subsequently which outcomes most of the commercially available CO2 sensors [65].The as prepared MWCNTs/ZnO by reflux method at 197 ºC in ethylene glycol is employed for methanol gas detection. A wide span of temperatures within 100-300 ºC was investigated for the sensing behavior where the best performance was gained at the latter CARBON NANO BASED MATERIALS AND THEIR COMPOSITES FOR GAS SENSING.. __________________________________________________________________________________________________________________ ________________________________________________ Egypt.…”
Section: Carbon Nanotubes/metal Oxides For Gas Sensingmentioning
confidence: 74%
“…Graphene deserves great attention as it has a large theoretical specific surface area (2630 m2g-1), high intrinsic mobility (200,000 cm2 v-1s-1), [65][66] high Young's modulus (*1.0 TPa) [67]and thermal conductivity (5000 Wm-1K-1), [68][69][70][71]optical transmittance (*97.7 %) and good electrical conductivity, on other hand, preparation of the large specific surface area, high quality is not applicable in a low cost-effective way.…”
Section: Synthesis Of Graphenementioning
confidence: 99%
“…Apart from the sensing modules discussed above, there are other types of gas sensors such as surface acoustic wave (SAW), 58 catalytic combustion, 59 and thermal conductivity 60 gas sensors. In brief, in SAW sensors, the properties ( i.e.…”
Section: Sensing Modules Of Nanomaterial-enabled Gas Sensorsmentioning
confidence: 99%
“…The measurements are accomplished using a Wheatstone bridge circuit against a flow of a reference gas on a second sensing element. 60 Fig. 1 outlines the major sensing methods used to detect critical gas molecules relevant to mining safety, as well as the contribution of nanomaterials in enhancing the performance and applicability of these sensors.…”
Section: Sensing Modules Of Nanomaterial-enabled Gas Sensorsmentioning
confidence: 99%
“…Thirdly, the CNTs have very high thermal conductivity, thus effectively improving the thermal conductivity of the ZnO/CNTs carrier material [68]. The high thermal conductivity accelerates the desorption of gas molecules, which improves the response time and stability of the sensor.…”
Section: Gas-sensing Mechanismmentioning
confidence: 99%